2006
DOI: 10.1074/jbc.m605623200
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor-binding Protein 1 Gene Is a Primary Target of Peroxisome Proliferator-activated Receptors

Abstract: Insulin-like growth factor-binding protein 1 (IGFBP-1) is a biomarker for metabolic and hyperproliferative diseases. At the same time, the nuclear receptors peroxisome proliferator-activated receptors (PPARs) are known for their critical role in the development of both the metabolic syndrome and various cancers. Here we demonstrate, in human hepatocellular carcinoma cells and in normal mouse liver, that IGFBP-1 mRNA expression is under the primary control of PPAR ligands. We applied an improved in silico scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 53 publications
5
52
0
Order By: Relevance
“…5B). In our study, the binding activity of PPAR␥ was not changed by rosiglitazone, and similar phenomena have been reported by other researchers (10,19). EMSA with in vitro-translated PPAR␥ and RXR␣ showed that they specifically bound to hGPx3 (Ϫ2186) PPRE (data not shown).…”
Section: Treatment Withsupporting
confidence: 73%
“…5B). In our study, the binding activity of PPAR␥ was not changed by rosiglitazone, and similar phenomena have been reported by other researchers (10,19). EMSA with in vitro-translated PPAR␥ and RXR␣ showed that they specifically bound to hGPx3 (Ϫ2186) PPRE (data not shown).…”
Section: Treatment Withsupporting
confidence: 73%
“…On the other hand, the Igfbp1 gene was downregulated to the largest extent in the mouse liver after exposure to isolation stress for 30 days in the DNA microarray analysis. Recently, Igfbp1 was reported to be a primary target gene of peroxisome proliferator activated receptors (PPARs) (11). The present study found that the Ppara-mediated signal pathway was downregulated in the liver under the social stress (Fig.…”
Section: Isolation Stress and Hepatic Gene Expression In Micesupporting
confidence: 53%
“…We observed that emodin elevated IGFBP1 protein and mRNA expression, one of PPARγ target genes [24], in A549 and H1975 cells (Fig. 4A-B).…”
Section: Resultsmentioning
confidence: 99%
“…Data for the link of IGFBP1 and lung cancer risk are sparse, whether the expression and function of IGFBP1 in stimulating or inhibiting lung cancer growth and progression remain elusive. Of note, early study found that IGFBP1 gene was one of primary targets of PPARs [24]. …”
Section: Introductionmentioning
confidence: 99%